2015
DOI: 10.1007/s13187-015-0888-y
|View full text |Cite
|
Sign up to set email alerts
|

YouTube™ as a Source of Instructional Videos on Bowel Preparation: a Content Analysis

Abstract: Instructional videos on bowel preparation have been shown to improve bowel preparation scores during colonoscopy. YouTube™ is one of the most frequently visited website on the internet and contains videos on bowel preparation. In an era where patients are increasingly turning to social media for guidance on their health, the content of these videos merits further investigation. We assessed the content of bowel preparation videos available on YouTube™ to determine the proportion of YouTube™ videos on bowel prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…This may explain the low number of high-content videos uploaded regarding medical issues. 15 However, there was no difference in total VIQI score between the high-and low-content video groups. This might be the result of following the evolving technology by YouTubee users.…”
Section: Discussionmentioning
confidence: 85%
“…This may explain the low number of high-content videos uploaded regarding medical issues. 15 However, there was no difference in total VIQI score between the high-and low-content video groups. This might be the result of following the evolving technology by YouTubee users.…”
Section: Discussionmentioning
confidence: 85%
“…YouTube™ does not impose any restriction or content control on medical videos; therefore, the content quality of medical videos is deficient. Patients may also find it challenging to apply information from videos [26]. Clinicians should keep in mind that even if the information given in the videos is correct, patients may not always be able to interpret it correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Videos can be copied directly to patients’ laptops or mobile phones, or be delivered through the internet. For example, several studies reported that YouTube, as the biggest online video website, has turned into a unique platform for patients to get BP health information.…”
Section: Enhanced Education Mainly For Promoting Comprehensionmentioning
confidence: 99%